Bridget Jones : mad about the boy [videorecording (Blu-Ray)] - Fielding, Helen, 1958-; Mazer, Dan; Morgan, Abi; Zellweger, Renée, 1969-; Ejiofor, Chiwetel; Woodall, Leo; Broadbent, Jim; Firth, Colin, 1960-; Grant, Hugh; O'Halloran, Dustin, 1971-; Lavelle, Suzie; Fielding, Helen, 1958- (Universal Studios, 2025)
Bridget, now a widowed single mother, must juggle work, parenthood and romance. With the help of her loyal friends, Bridget navigates encounters with a younger man and a series of awkward interactions with her son's science teacher as she strives to forge a new path toward life and love.